Transmedia Festivals and the Accelerated Cultural Sector - Bianca Kristina Ludewig (IASPM Journal, 2019)
Over the past couple of decades, urban transmedia festivals have gained a distinct presence in the European cultural landscape, constituting an alternative to other, more dominant, conceptions of music festivals. This article introduces transmedia festivals as a new type of contemporary festival and situates them in wider urban processes. Transmedia festivals originated on the fringes of new urban scenes, in which media art was overlapping with electronic music and club culture. Based on multi-year field research, this article argues that these festivals have become part of urban renewal processes. The core focus of this article is therefore how transmedia festivals are part of processes such as eventization, culturalization, precarization, and gentrification. Local and EU-funding-policies, moreover, impose opportunities and dilemmas on urban festivals. The article is a contribution to the still small area of cultural and urban studies on such festivals in Europe, and situates transmedia festivals within urban cultural change.